From Australian Influence to Rohingya Refugees: A Systematic Literature Review of Asylum Seekers and Refugees in Indonesia - Dewansyah, Bilal (The Indonesian Journal of Socio-Legal Studies, 2025)
The fact that Indonesia hosts asylum seekers and refugees attracted not only policy debate and media attention but also academic research. However, no systematic review has been conducted to assess the scholarly literature on this topic. This article is intended to fill this gap by presenting a systematic literature review (SLR) on asylum seekers and refugees in Indonesia. As a result, I found five major themes in the reviewed literature: (1) the focus on the Indonesia – Australia relationship; (2) people smuggling; (3) refugees’ journey and living conditions in Indonesia; (4) Rohingya refugees; (5) legal protection and refugee status. However, this review also found some topics understudied as avenues for further research, such as the policy-and-lawmaking process, and the officials’ discretion or discretionary decision-making in implementing law and policy related to refugees, as well as the role of religion and ethnicity in law and policy on this matter. More importantly, this body of literature informs valuable findings, such as refugees’ self-surrender to the immigration detention centers and an acute silos tendency in Indonesian refugee governance that can contribute to the theoretical debate in this field.